Jehovah’s Witness Needing Critical Care: A Narrative Review on the Expanding Arsenal - Ryan Davids; Gareth Robinson; Charmé Van Tonder; Jordan Robinson; Nadiyah Ahmed; Abdurragmaan Domingo (Critical Care Research and Practice)
Present day Jehovah’s Witness (JW) religion accounts for 8.5 million followers. A tenant feature of the JW faith is religious objection to transfusions of blood and blood products. Interpatient variability, as it pertains to blood and blood products may occur; hence, a confidential interview will determine which products individual may consent to (Marsh and Bevan, 2002). This belief and practice place great restrictions on treating medical professionals in scenarios of life-threatening anaemia and active haemorrhage. The review to follow explores the physiological and pathophysiological consequences of severe anaemia. Non-blood transfusion practices are explored, many of which are potentially lifesaving. Particular attention is drawn to the evolving science involving artificial oxygen carriers and their use in emergency situations. A greater safety profile ensures its future use amongst religious objectors to be greatly beneficial. Intravenous iron supplementation has enjoyed a lively debate within the critical care community. A review of recent systematic and meta-analysis supports its use in the ICU; however, more investigation is needed into the complementary use of hepcidin.